2012
DOI: 10.1111/j.1365-2966.2012.20972.x
|View full text |Cite
|
Sign up to set email alerts
|

Galaxy Zoo: the environmental dependence of bars and bulges in disc galaxies

Abstract: We present an analysis of the environmental dependence of bars and bulges in disc galaxies, using a volume‐limited catalogue of 15 810 galaxies at z < 0.06 from the Sloan Digital Sky Survey with visual morphologies from the Galaxy Zoo 2 project. We find that the likelihood of having a bar, or bulge, in disc galaxies increases when the galaxies have redder (optical) colours and larger stellar masses, and observe a transition in the bar and bulge likelihoods at M*= 2 × 1010 M⊙, such that massive disc galaxies ar… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

21
124
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 120 publications
(145 citation statements)
references
References 151 publications
21
124
0
Order By: Relevance
“…As shown in tal dependence between bars/bulges likelihood with environment (e.g. Skibba et al 2012) would appear to be linked to the presence of gaseous components in group galaxies.…”
Section: On Correlations Between Galaxy Properties and Host Halo Massmentioning
confidence: 99%
“…As shown in tal dependence between bars/bulges likelihood with environment (e.g. Skibba et al 2012) would appear to be linked to the presence of gaseous components in group galaxies.…”
Section: On Correlations Between Galaxy Properties and Host Halo Massmentioning
confidence: 99%
“…A number of studies have been dedicated to understanding the effects of the environment on bar formation (e.g. Aguerri et al 2009;Li et al 2009;Barazza et al 2009;Méndez-Abreu et al 2010Skibba et al 2012;Lin et al 2014). While it is reasonable to consider the possibility that the bar in NGC 4371 is the result of an interaction, since the galaxy is in a dense environment, this is a difficult claim to defend.…”
Section: The Onset Of Bar-driven Secular Evolution In Cosmic Historymentioning
confidence: 99%
“…More recently, Skibba et al (2012), also using clustering statistics, reported a positive correlation for bulge-dominated and barred galaxies to be found in denser environments on scales of 150 kpc to a few megaparsecs than their unbarred and diskdominated counterparts and argued that barred galaxies are often central galaxies in low-mass dark matter halos or satellites in more massive ones. Lee et al (2012a) also investigated the dependence of the barred galaxy fraction on environment, finding that once mass and color are fixed, the bar fraction is independent of the background density, but an influence of the nearest neighbor appears when the separation to the nearest neighbor is less than 0.1 times the virial radius of the neighbor.…”
Section: Introductionmentioning
confidence: 99%